The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1093/jhered/esm107
|View full text |Cite
|
Sign up to set email alerts
|

Sex Identification of Owls (Family Strigidae) Using Oligonucleotide Microarrays

Abstract: Molecular sexing of the diversified avian family Strigidae is difficult. Sex identification using the intron length difference between W and Z chromosomal CHD1 genes, as visualized by agarose gel electrophoreses, often produces ambiguous results. Here we describe a simple method for sexing a variety of Strigidae species using oligonucleotide microarrays, on which several sex-specific probes operated complementarily or in concert. The sex of 8 owl species was identified clearly on the microarrays through sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…It also provides an advantage of customized probe spotting. The reliability of the PVC biochip has been proven in several applications; e.g., the simultaneous detection and differentiation of seven mastitis-causing pathogens in bovine milk samples [37], Newcastle disease and avian influenza in the poultry industry [42], and Cymbidium mosaic virus , Odontoglossum ringspot virus and CaCV for orchid inspection (Dr. Orchid-3™ Kit, Dr. Chip), and the identification of insect species [43] and the sex of owls [44]. …”
Section: Discussionmentioning
confidence: 99%
“…It also provides an advantage of customized probe spotting. The reliability of the PVC biochip has been proven in several applications; e.g., the simultaneous detection and differentiation of seven mastitis-causing pathogens in bovine milk samples [37], Newcastle disease and avian influenza in the poultry industry [42], and Cymbidium mosaic virus , Odontoglossum ringspot virus and CaCV for orchid inspection (Dr. Orchid-3™ Kit, Dr. Chip), and the identification of insect species [43] and the sex of owls [44]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for accurate sex identification in these species alternative gametologs such as NIPBL or alternative CHD1 based primers might be used (Suh et al, ). It has recently been shown that high resolution melting curve (HRM) real time PCR and oligonucleotide microarrays may be useful for accurate sex identification in Strigidae (Morinha et al, ; Wang et al, ). P2/P3 is another CHD1 ‐specific primer that has been used for sex identification in birds of prey.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, X and Z chromosomelinked loci are not usually used as stand-alone techniques for animal sex determination (Dubiec & Zagalska-Neubauer 2006). Sexing technique methods are usually based either on the presence or absence of PCR amplification products, on the differences in band lengths and/or the resulting banding patterns on gel, and/or on differences in sequences ('qualitative sexing'), which enable researchers to distinguish between X and Y chromosomes (mammals) or W and Z chromosomes (birds) [restriction fragment length polymorphisms (RFLPs, Sacchi et al 2004), amplified fragment length polymorphism (AFLPs, Griffiths & Orr 1999), single strand conformation polymorphism (SSCPs, Ramos et al 2009), microsatellite alleles (Nesje & Roed 2000), and oligonucleotidemicroarrays (Kalz et al 2006;Wang et al 2008)]. …”
Section: Introductionmentioning
confidence: 99%